An Analysis of Dzikrayat Muslim Fashion Business Development Strategy With Canvas Business Model Approach In Ponorogo Regency, East Java - Zarkasy, Muhammad Ridlo; Kurniawan, Dhika Amalia; Zuhri , Ahmad Syaifudin (SENTRALISASI, 2024)
This research aims to develop a strategy for Dzikrayaat Muslim fashion business using a business model canvas (BMC). This used a descriptive qualitative method with SWOT analysis by samples of 4 stakeholder respondents and customers. The results show from a key partner perspective, Dzikrayaat needs to collaborate with brand ambassadors, Darussalam Gontor Boarding School graduates as new partners, agents, and distributors in marketing. From the perspective of key activities, the strategy can be done by adding product variations such as robes, headscarves, and other Muslim attributes. From the perspective of value proposition, adding the size of Muslim clothing is necessary. From the sector of customer relationships, it needs to give membership card and discount to loyal customers. For the customer segments, it adds a market of women or young mothers who are interested in Muslim fashion. From the key resources side, they have their cohesion and professional tailors. From the channels, it needs to start an online shop in the marketplace. From the perspective of revenue stream, it utilizes fabric waste for sale. Therefore, according to those results, researchers have some suggestions such as developing a strategy by adding some components to nine business blocks of the canvas model.